A RANDOMIZED CONTROLLED TRIAL OF LIFE-MODIFICATION INTERVENTION FOCUSED ON REDUCING ALCOHOL INTAKE TO CONTROL THE HYPERTENSION IN MALE PATIENTS DURING OUTPATIENT VISIT: OSAKE STUDY. (April 2021) - Kabayama, Mai; Akagi, Yuya; Tamatani, Michio; Tomita, Jun; Takiuchi, Shin; Yamamoto, Koichi; Sugimoto, Ken; Rakugi, Hiromi; Kamide, Kei
Abstract : Objective: To verify the effectiveness of the nurse-led life-modification intervention focused on reducing alcohol in male patients with hypertension during outpatient visit. Design and method: We enrolled 53 male patients (20–74years old) with morning home blood pressure (HBP) of 135/85 mmHg or more with excessive drinking (alcohol > = 210 g/week or > = 60 g/day habitually) from outpatient visit (at University hospital, General hospital, and Clinic setting) in a randomized controlled trial. Patients were assigned to a nurse-led intervention (in which patients were encouraged to modifying the alcohol consumption to optimal level in addition to the usual treatment every 2 month) or to the control (in which patients were followed see by their doctor as usual). The primary outcome were mean morning HBP of 5 consecutive days at 6 months and the amount of alcohol consumption. The HBP was measured by OMRON EM7251G and recorded on the Medical link Website. Results: The number of patients randomized to intervention were 28 and control were 25 (mean age; 62.7 ± 8.8years old, 64.5 ± 5.9 respectively), and 1 patient drooped-out in each group. At baseline, the mean HBP was 143/90 mmHg in the intervention group and 144/88 mmHg in the control (n.s.). At 6 months, the mean HBP was 131/82 mmHg in the intervention group and 145/87 mm Hg in the control (SBP < 0.001, DBP = 0.09). HBP level of less than 135/85 mmHg was achieved among 55.6% of the participants in the intervention group versus 16.7% in the control (P = 0.004). At baseline, the weekly alcohol consumption was 479 ± 353 g in the intervention group and 360 ± 182 g in the control (n.s.). At 6 months, it was 256 ± 206 g in the intervention group and 413 ± 260 g in the control (p = 0.020). Conclusions: We confirmed the effectiveness of the nurse-led life-modification intervention focused on reducing alcohol intake to control the morning HBP in male patients with hypertension as a method of non-pharmacological treatment during outpatient visit.